forall x Calgary - Magnus, P.D; Button, Tim; Trueman, Robert; Zach, Richard; Loftis, J. Robert; Thomas-Bolduc, Aaron (Open textbook library., 2023)
forall x: Calgary is a full-featured textbook on formal logic. It covers key notions of logic such as consequence and validity of arguments, the syntax of truth-functional propositional logic TFL and truth-table semantics, the syntax of first-order (predicate) logic FOL with identity (first-order interpretations), symbolizing English in TFL and FOL, and Fitch-style natural deduction proof systems for both TFL and FOL. It also deals with some advanced topics such as modal logic, soundness, and functional completeness. Exercises with solutions are available. It is provided in PDF (for screen reading, printing, and a special version for dyslexics), HTML (with additional accessibility features), and in LaTeX source code.